Effect of hormone treatment on oestrus response in prepubertal indigenous goats of Assam - HASIN, DILRUBA; BARUAH, K K; CHAKRAVARTY, P; BISWAS, R; SARMAH, B C; BARUAH, ANUBHA (The Indian Journal of Animal Reproduction, 2023)
Six indigenous prepubertal goats aged 6 months of age were fed medroxy progesterone acetate (MAP) orally @ 5 mg/ animal/day for 13 days followed by intramuscular injection of 650 l.U. of PMSG on the day of withdrawal of progesterone. The . animals exhibited oestrus within 42.88±3.84 hours after PMSG injection. However, another 6 indigenous prepubertal goats received · sterile normal saline treatment, exhibited oestrus after 50.83±6.63 days of saline treatment. The age and body weight at first oestrus in hormonally treated and saline treated groups of animals were 199.79±1.66 days and 6.68±0.09 kg, respectively and 233.33±5.74 days and 7.95±0.15 kg, respectively.